(untitled) (International Journal of Environmental Sciences, 2025)
Cancer is an increasingly significant health issue globally, resulting in a rise in the use of chemotherapy, which remains the primary and most common treatment for malignant tumors. This study aims to examine the histopathological changes and immunological responses to assess the toxic effects of Taxol. Specifically, it investigates how the anti-cancer drug Taxol impacts the histological and immunological characteristics in laboratory rats. The rats were randomly divided into three groups, each group containing 12 laboratory rats, as follows Control group: Consists of 12 rats. This group was injected with 0.5 ml of distilled wat Low dose group: Consists of 12 rats injected with a concentration of 2mg/kg of TAXOL intraperitoneally High dose group: Consists of 12 rats injected with a concentration of 4mg/kg of TAXOL intraperitoneally. Histological examination of tissue sections revealed pathological changes in the livers of laboratory rats. Specifically, liver samples from rats treated with Taxol exhibited necrosis and degeneration of hepatic cells, along with infiltration of inflammatory cells. Some hepatic cells showed distorted and enlarged nuclei, as well as hyperpigmentation of the cytoplasm. Additionally, there was an expansion and congestion of the hepatic portal vein and hepatic sinusoids. Laboratory analyses conducted using ELISA indicated that the low-dose group experienced a significant increase in IL-8 levels, whereas the high-dose group showed a notable decrease in interleukin 8 levels in the blood serum. The current study revealed that Taxol has a significant effect on liver tissue, leading to noticeable changes and differing immune responses based on the dosage administered